Quantitative chemical analysis - Harris, Daniel C. (New York : W.H. Freeman and Company, 2003)
This comprehensive introduction to the tools and techniques of analytical chemistry has been thoroughly revised to include contemporary research. The sixth edition also includes new chapters, a website, and it incorporates real data, spreadsheets and a wealth of applications.